Distributed Electric System Control Strategy Optimization. Issue 1 (March 2020) - Chen, Chunping; Wang, Jie; Zhang, Jie
Abstract: With the increasing energy crisis and environmental pollution, this paper concentrates on the energy management and power control of DC microgrid due to its advantage in the utilization of renewable energy resources (RES). However, the traditional centralized control relies heavily on communication since the distribution of most RES is scattered, and the communication failures may cause serious control error, therefore, a distributed and cooperative control strategy without communication is proposed for DC microgrid in this paper. The proposed strategy not only maintains the bus voltage and power balance in a cooperative way through the regulation of each micro-sources, but also solves theunbalance problem between ESUs, meanwhile, this method is suitable for DC microgrid with multiple PVs and ESUs since the communication is not necessary, which is benefit for the plug and in of micro-sources. Finally, some simulation models are built on Matlab/Simulink platform, and the performance of suggested solution is verified through a set of simulation experiments, the result turns out to be good and confirms our expectation.